Enhancing beginner learners' oral proficiency in a flipped Chinese foreign language classroom. Issue 5 (4th July 2018) - Wang, Jun; An, Na; Wright, Clare
ABSTRACT: Flipped instruction has become a hot issue in foreign language teaching technology. In this study, we tracked learners in a beginner-level Chinese Foreign Language classroom to see if flipped teaching based on a MOOC made a difference to their oral proficiency development and rate of progresscompared to a baseline group. Language developmentwas assessed by standard complexity, accuracy and fluency measures, alongside subjective ratings. Learners' investment of time and perceptions of the new method were also investigated. Results showed that learners exposed to flipped instruction significantly (p < .01) outperformed the baseline group in oral proficiency in many measures, especially in speech fluency, though their advantage in complexity and accuracy was less evident. Rate of progress through the syllabus for the flipped group was also faster, requiring 25% less face-to-face time. Learners in the flipped group also demonstrated more (out of class) time investment in their learning and more positive attitudes toward the course, though these two factors did not significantly associate with the proficiency measures. These results support the implementation of flipped instruction in foreign language classrooms for both better and faster learner improvement; we explore how far psycho-social models of active learning might explain its methodological advantages.